2020
DOI: 10.1038/s41598-020-58419-3
|View full text |Cite
|
Sign up to set email alerts
|

1RS arm of Secale cereanum ‘Kriszta’ confers resistance to stripe rust, improved yield components and high arabinoxylan content in wheat

Abstract: Wheat-rye T1BL.1RS translocation is widespread worldwide as the genes on 1RS arm have positive effect on stress resistance, grain yield and adaptation ability of wheat. Nowadays, the T1BL.1RS wheat cultivars have become susceptible to rust diseases because of the monophyletic ('Petkus') origin of 1RS. Here we report and discuss the production and detailed investigation of a new T1BL.1RS translocation line carrying 1RS with widened genetic base originating from Secale cereanum. Line '179' exhibited improved spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 82 publications
0
21
0
4
Order By: Relevance
“…Kriszta, и за счет рекомбинации между хромосомами T1BL.1RS и 1R в пшеницу были введены новые аллели генов ржи (Molnár-Láng et al, 2010). Одна из таких рекомбинантных форм дала начало линии M9kr1-Kriszta T1BL.1RS line 179, обладающей устойчивостью к желтой и бурой ржавчинам в сочетании с высоким качеством зерна (Szakács et al, 2020). При использовании совместимых с рожью местных китайских сортов пшеницы Mianyang 11 и A42912 были также созданы линии с T1BL.1RS от разных сортов ржи, которые содержали новые эффективные аллели генов ус тойчивости к расам Puccinia striiformis f. sp.…”
Section: генетические ресурсы созданные при скрещивании мягкой пшеницы с рожью и их использование в селекцииunclassified
“…Kriszta, и за счет рекомбинации между хромосомами T1BL.1RS и 1R в пшеницу были введены новые аллели генов ржи (Molnár-Láng et al, 2010). Одна из таких рекомбинантных форм дала начало линии M9kr1-Kriszta T1BL.1RS line 179, обладающей устойчивостью к желтой и бурой ржавчинам в сочетании с высоким качеством зерна (Szakács et al, 2020). При использовании совместимых с рожью местных китайских сортов пшеницы Mianyang 11 и A42912 были также созданы линии с T1BL.1RS от разных сортов ржи, которые содержали новые эффективные аллели генов ус тойчивости к расам Puccinia striiformis f. sp.…”
Section: генетические ресурсы созданные при скрещивании мягкой пшеницы с рожью и их использование в селекцииunclassified
“…Recently, the detection of rye translocation lines, present in the bread wheat Pavon, with elevated Zn and Fe content has been reported by Velu et al [18], whereas Szakács et al [19] using a new 1RS/1BL translocation line, whose 1RS arm originated from the perennial Secale cereanum, found that the novel translocation had improved spike morphology traits, higher tillering capacity, fertility, winter hardiness and resistance against stripe rust and leaf rust. In addition, a large increase in arabinoxylans content (both total and water soluble) was found, compared to the parental bread wheat genotype improving the nutritional value of the material containing the novel 1RS/1BL translocation line.…”
Section: Qualitative Analysesmentioning
confidence: 99%
“…Rye represents an important source of useful alien genes for wheat improvement, and at this regard the intergeneric introgressions of the Robertsonian 1BL/1RS wheat-rye translocation represents one of the most successful achievement, as also witnessed by the high number of wheat variety released worldwide [16]. In this material the short arm of wheat chromosome 1B is replaced by its counterpart from the rye genome which arose spontaneously from centromeric breakage reunion and fusion of two chromosome arms broken at the centromere conferring to wheat resistance to several diseases, high yield performance, wide adaptation, resistance to drought, increasing amount of micronutrient, protein content and arabinoxylan content [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, only five are of particular economic importance, including 1BL/1RS translocation, to a lesser extent -1АL/1RS. The provenance 1BL/1RS translocation is the soft winter wheat selected lines Riebesel 47-51, derived from rye variety Petkus (Szabo & Kolmer, 2007;Szakács et al, 2020). The source of 1AL/1RS translocation is the Amigo wheat variety, which received it from the Argentine rye variety Insave (Kozub et al, 2018).…”
Section: Parameters Of Adaptability Biological and Economically Valumentioning
confidence: 99%
“…This is especially true for Ukraine, it declares itself on the world market the everincreasing volume of grain exported. Unfortunately, Ukrainian wheat in general is inferior in grain quality to the best world varieties and often does not fully satisfy the national market the level of quality of wheat flour (Rybalka, 2011;Szakács et al, 2020) in the selection of soft winter wheat homogeneous genetic material, besides progress in increasing productivity varieties, caused a narrowing of their genetic basis and an increasing the affinity of the gene pool (Ivanova et al, 2019). This led to that the vast majority of domestic varieties have a narrow technological direction of using (Rybalka, 2011;Kozub et al, 2018;Motsny, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%